2015
DOI: 10.18579/jpcrkc/2015/0/0/79203
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fixed Low Dose Rasburicase in the Prevention and Treatment of Tumor Lysis Syndrome

Abstract: Tumour Lysis Syndrome (TLS) is a serious complication of malignancies and can result in renal failure or death. Hyperuricaemia is one of the prominent features of TLS which if not adequately prevented or treated can lead to renal failure requiring dialysis.Rasburicase is the most recent agent indicated for treating TLS which is a recombinant urate oxidase enzyme that will oxidize uric acid to allantoin, a metabolite with 5-10 fold greater solubility than uric acid and reduces serum uric acid (SUA) levels withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Studies from India have used single dose based on body weight and with small sample size in the pediatric age group [10,16,17]. Our study shows similar results to another study from India using single 1.5 mg fixed dose of rasburicase [11]. In the group with clinical TLS the median dose of rasburicase delivered per case was 2.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies from India have used single dose based on body weight and with small sample size in the pediatric age group [10,16,17]. Our study shows similar results to another study from India using single 1.5 mg fixed dose of rasburicase [11]. In the group with clinical TLS the median dose of rasburicase delivered per case was 2.…”
Section: Discussionsupporting
confidence: 84%
“…The recommended dose of rasburicase is 0.15-0.2 mg/kg per day for 5 days for TLS management. Studies have shown much lesser doses to be effective in preventing TLS [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%